PENINGKATAN KAPASITAS SUMBER DAYA KELURAHAN LENGKONG KARYA, MELALUI SOSIALISASI UNDANG-UNDANG NO. 16 TAHUN 2011 TENTANG BANTUAN HUKUM, SEBAGAI UPAYA BERSAMA PEMENUHAN AKSES KEADILAN BAGI MASYARAKAT MISKIN - Halimah Humayrah Tuanaya; Abdul Hayy Nasuiton; Wahib Wahib; Dian Eka Prastiwi; Mohamad Fandrian Hadistianto (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
The provision of legal aid is one way to realize access to justice for the poor given by the state on the mandate of the constitution. Several regulations regarding legal aid have been issued by the state through the law and implementing regulations. The most explicit statutory provisions governing the provision of legal assistance are Law No. 16 of 2011 concerning Legal Aid. But the facts in the community, the regulations that have been made have not been effectively implemented so that the meaning of access to justice is biased. The ineffectiveness of the application of legal aid in Indonesia is an interesting legal issue to be followed up immediately to make effective the provision of legal aid in order to realize access to justice for the poor. Based on the Memorandum of Understanding (MoU) that was signed between the Faculty of Law at the University of Pamulang with the District of North Serpong, then as a follow up is the implementation of Community Service (PKM) in all sub-district in the Serpong Utara District, one of which is Lengkong Karya Sub-District. This is one form of the implementation of the Tri Dharma of Higher Education which is an obligation of the academic community of Pamulang University. Lack of socialization and access to information on free legal assistance for the poor among the increasing number of people who are in conflict with the law, either because they are victims, perpetrators, or witnesses of criminal cases, such as murder, theft, etc., or become parties to civil matters such as divorce, inheritance, land disputes, etc. So that this legal counseling activity is very urgent to do in order to guarantee the rights of the poor to legal assistance in accordance with the mandate of Law No. 16 of 2011 concerning Legal Aid. This journal is a mandatory output from PKM that has been conducted in accordance with PKM Edition XII guidelines. PKM activities have been carried out on 9-11 October 2019. Located in the Lengkong Karya Village Head Office, with staff members from the Lengkong Karya sub-district and other community groups, such as women who are administrators of Family Welfare Empowerment (PKK). There are two stages of the method of implementing PKM; First, the preparation stage which contains surveys and preparation of activity material; Second, the implementation phase is carried out using two methods, namely counseling and discussion.Key Words: Legal Aid, Access to justice